Thermally oxidized aluminum as catalyst-support layer for vertically aligned single-walled carbon nanotube growth using ethanol - Mohd Abid, Mohd Asyadi Azam (Elsevier, 2011)

(untitled)
Characteristics and role of Al oxide (Al-O) films used as catalyst-support layer for vertical growth of single-walled carbon nanotubes (SWCNTs) were studied. EB-deposited Al films (20 nm) were thermally-oxidized at 400 oC (10 min, static air) to produce the most appropriate surface structure of Al-O. Al-O catalyst-support layers were characterized using various analytical measurements, i.e., atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and spectroscopy ellipsometry (SE). The thermally-oxidized Al-O has a highly-roughened surface, and also has the most suitable surface chemical states compared to other type of Al-O support layers. We suggest that the surface of thermally-oxidized Al-O characterized in this work enhanced Co catalyst activity to promote the vertically-aligned SWCNT growth.